Integration of transcriptomic and proteomic data uncovers the nutritional requirement of the immature development of an endoparasitoid wasp - Li-Zhi Wang; Zi-Han Wang; Shuang Xie; Peng-Zhan Wang; Xi-Qian Ye; Jian-Hua Huang; Zhi-Zhi Wang; Xue-Xin Chen (Scientific Reports)
Abstract Endoparasitic wasps produce several factors, such as polydnavirus, venom and a specialized group of wasp embryonic cells named teratocytes, to condition their hosts and support the development of parasitoid offspring. However, the role of the developing parasitoid larvae in host adaption and regulation remains largely unknown. By analyzing RNA-seq data of Cotesia vestalis, an endolarval parasitoid of the diamondback moth Plutella xylostella, we discovered that most of the larval stage highly expressed genes are associated with nutrient metabolism, including carbohydrate, protein, and lipid metabolism. We also identified hundreds of C. vestalis larvae-secreted proteins. A large proportion of the secreted proteins (126/404) are encoded by larval highly expressed genes. Besides several immune-related proteins, most of the secreted proteins are closely related to carbohydrate, protein, and amino acid metabolism. We further demonstrated that eleven genes linked to amino acid metabolism that encode secretory proteins were upregulated in 2nd instar larvae. These results suggest a relatively positive correlation between gene expression and secreted proteins. In summary, our study presents the secretory proteome of an endolarval parasitoid, highlighting its potential function in nutritional and immune regulation within the host, which would benefit the growth and development of parasitoid progeny.